Modified "Roux en Y" hepaticojejunostomy to permit transgastric endoscopic access - Moricz,André de (2014)
PURPOSE: To present an option technique during the accomplishment of a "Roux-en-Y" hepaticojejunostomy that, allows future transgastric endoscopic access to the biloenteric anastomosis. METHODS: The side-to-side "Roux-en-Y" hepaticojejunostomy is carried through transmesocolic, retrogastric short tunnel. A distal jejunal loop of approximately 10,0 to 15,0 cm must be kept far from the anastomosis that allows its setting, without tension, in the anterior gastric wall bellow the small bending, between body and of the stomach antrum. Once the jejunal segment is fixed on the anterior gastric wall, this will allow future endoscopic access to the bilioenteric anastomosis, carried through transgastric punction guided by endoscopic-ultrasound (EUS). CONCLUSION: The modified "Roux en Y" hepaticojejunostomy is a simple and new technique to permit an alternative transgastric endoscopic access to bilioenteric anastomosis.